Glukagonom - Mušič, Mark (Medicinski razgledi, 2003)
Glucagonoma is a rare neuroendocrine tumor with pancreatic alpha cell differentiation. This tumor is characterized by hypersecretion of a peptide hormone glucagon, which can be detected in this type of neoplasia. The majority of tumors are malignant and most patients already have a metastasis. The average patient age at the time of tumor discovery is 52.5 years. A characteristic, although not a pathognomonic sign of the tumor is a skin rash in the form of necrolytic migratory erythema. Along with diabetes or glucose intolerance, weight loss or cahexia, thromboembolic problems, anemia and diarrhea are the main signs of glucagonoma syndrome. In our case. A 53-year-old female patient had all of the major characteristic signs of glucagonoma syndrome, the diagnosis of which was delayed for three years. She was successfully operated on. No signs of abdominal metastases were found during surgery. Shortly after surgery, she was free of all symptoms. The histopathological examination revealed a benign, neuroendocrine tumor with a positive reaction to glucagon. Conclusion. One should be suspicious of this tumour in all patients with chronic erythema, especially in combination with other symptoms of glucagonoma syndrome. Early diagnosis is very important for improving the patient's survival and quality of life. The only successful treatment is complete surgical excision of the tumour. Ten year survival ratesfor a small number of patients with a limited disease have been calculated to be 64% and for those with metastases about 50%.
Keywords: Glucagonoma; Glukagonom; Pancreatic Neoplasms; Trebušna slinavka, novotvorbe; Anemija; Middle Age; Eritem kronični, migracijski; Skin Diseases; Erythema Chronicum Migrans; Kaheksija; Kožne bolezni; Diabetes Mellitus; Cachexia; Sladkorna bolezen; Srednja leta; Anemia; Thromboembolism; Tromboembolija; rak (medicina); trebušna slinavka; novotvorbe; tumor